Novelties in Cheilolejeunea (Spruce) Steph. sect. Trachylejeunea (Lejeuneaceae: Jungermanniopsida) from the Brazilian Amazon - Bastos, Cid José Passos; Sierra, Adriel M.; Zartman, Charles E.; Schäfer-Verwimp, Alfons (Phytotaxa, 2025)
Two new species of Cheilolejeunea in the section Trachylejeunea from the State of Amazonas, Brazil, are described and illustrated. The new species are characterized by a pyriform perianth, absence of innovations, presence of two teeth at the apex of the leaf lobule and strongly mammillose cells along the keel. The similarities with Cheilolejeunea aneogyna and with Cheilolejeunea papulosa are discussed. The holotype of Pycnolejeunea remotistipula was studied for comparison with the new proposed species; however, this study allowed us to conclude that P. remotistipula belongs to Cheilolejeunea Sect. Trachylejeunea thus justifying a new combination.